KOORDINASI PROGRAM PEMBAGUNAN MAHYANI DI DESA LUHUTO KECAMATAN BIAU KABUPATEN GORONTALO UTARA - Luawo, Salma Rivani; Karim, Dian Fitriani; Alwaris (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This study examines the coordination of the Mahyani development program in Luhuto Village, Biau Subdistrict, Gorontalo Utara Regency. The Mahyani program, aimed at providing decent housing for low-income families, plays a significant role in improving the quality of life and addressing social welfare issues. This research focuses on the effectiveness of coordination among stakeholders, including local government, community leaders, and program beneficiaries, in achieving program goals. A qualitative approach is employed, using interviews, observations, and document analysis to collect data. The findings reveal that while the program has successfully constructed several housing units, challenges such as communication gaps, delays in fund disbursement, and limited community involvement hinder its overall effectiveness. The study emphasizes the importance of transparent and structured coordination mechanisms to ensure the sustainability and impact of the Mahyani program. This research contributes to the discourse on housing development programs by highlighting the critical role of coordination in program implementation, particularly in rural areas. Recommendations include enhancing stakeholder collaboration, capacity building for program implementers, and adopting participatory approaches to foster community engagement in future projects